THE IMPORTANCE OF EDUCATION - Berdiqulova Mahbuba Erkinjon qizi,; Ne’matova Durdona Shokirali qizi, (TADQIQOTLAR, 2026)
ABSTRACT Education plays a vital role in the development of individuals and society. It helps  people  gain  knowledge,  improve  their  skills,  and  build  a  successful  future. Educated  individuals  can  contribute  positively  to  the  economy  and  social  life. Moreover, education promotes critical thinking, creativity, and awareness. In today’s rapidly  changing  world,  education  is  essential  for  personal  growth  and  global development.